1985
DOI: 10.1037/0735-7044.99.6.1089
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of autonomic and behavioral components of conditioned fear during development in the rat.

Abstract: Classical conditioning of heart rate (HR) was examined in unrestrained preweanling and weanling (16-, 19-, 21-, 25-, and 28-day-old) rats, with tone and light as the conditioned stimuli (CS) and electric shock as the unconditioned stimulus. The conditioned cardiac response was a sustained deceleration in HR which did not emerge until Day 21 for the tone CS and until Day 28 for the light CS. In contrast, when suppression of a behavioral response (running in a straight alley for dry suckling as reward) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
61
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 28 publications
16
61
0
Order By: Relevance
“…A. Campbell & Ampuero, 1985). Taken together, these results confirm the general principle put forth by many investigators (Harlow, 1959;Piaget & Inhelder, 1969;Rudyet al, 1984) that simple types of leaming emerge earlier in development than do more complex forms.…”
Section: Discussionsupporting
confidence: 85%
“…A. Campbell & Ampuero, 1985). Taken together, these results confirm the general principle put forth by many investigators (Harlow, 1959;Piaget & Inhelder, 1969;Rudyet al, 1984) that simple types of leaming emerge earlier in development than do more complex forms.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the animals were able to learn about an auditory cue at a younger age than they were able to learn about a visual cue. This sequential development of learning across different sensory systems is a robust finding in the developmental literature (e.g., Alberts, 1984;Campbell & Ampuero, 1985;Hunt & Campbell, 1997).…”
mentioning
confidence: 65%
“…This window (generally occurring between 2 and 3 wk after birth) is common for many different paradigms such as different forms of Pavlovian fear conditioning and eyeblink conditioning (Campbell and Ampuero 1985;Moye and Rudy 1985;Paczkowski et al 1999;Raineki et al 2009). Moreover, studies of Pavlovian fear conditioning in infant hooded rats have found a dissociation in time between the ability to first detect visual events and to use these for associative learning (Moye and Rudy 1985).…”
Section: Discussionmentioning
confidence: 99%
“…While there are studies that have followed the ontogeny of learning behaviors in animal model systems of classical conditioning paradigms (Campbell and Ampuero 1985;Moye and Rudy 1985;Paczkowski et al 1999;Raineki et al 2009), the ontogeny of operant learning, in particular, remains much less explored.…”
mentioning
confidence: 99%